Structure of the CAC1 gene and in situ characterization of its expression. The Arabidopsis thaliana gene coding for the biotin-containing subunit of the plastidic acetyl-coenzyme A carboxylase. - Ke, J (1997)
The CAC1 gene of Arabidopsis thaliana that codes for the biotin carboxyl-carrier subunit of the heteromeric acetyl-coenzyme A carboxylase was isolated and sequenced. CAC1 is a single-copy gene interrupted by six introns. Subcellular immunogold labeling indicates that the biotin carboxyl-carrier subunit is localized in the stroma of the plastids and chloroplasts. The CAC1 mRNA accumulates throughout developing embryos and ovules of siliques at a time of rapid growth and oil accumulation (7 d after flowering), but is present at much lower levels in wall cells and central septal cells of the silique. Immunolocalization studies show that the pattern of accumulation of the biotin carboxyl-carrier subunit within the siliques and leaves is similar to that of the CAC1 mRNA. These observations indicate that the cellular pattern of biotin carboxyl-carrier protein accumulation in the developing silique may be determined by the transcriptional activity of the CAC1 gene.